Global, Regional, and National Burden of Cancer in Children Younger Than 5 Years, 1990–2019: Analysis of the Global Burden of Disease Study 2019 - Ren, Hui-Ming; Liao, Min-Qi; Tan, Si-Xian; Cheng, Chen; Zhu, Sui; Zheng, Lu; Ma, Jun-Rong; Mu, Ying-Jun; Li, Wan-Lin; Zhang, Shi-Wen; OuYang, Rui-Qing; Li, Shu-Na; et al. (Frontiers in Public Health, 2022)
Abstract Objectives: To quantify the burden and variation trends of cancers in children under 5 years at the global, regional, and national levels from 1990 to 2019. Methods: Epidemiological data for children under 5 years who were diagnosed with any one childhood cancer were obtained from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) from 1990 to 2019. The outcomes were the absolute numbers and rates of incidence, prevalence, mortality, and disability-adjusted life-years (DALYs) for different types of cancer. Results: In 2019, 8,774,979.1 incident cases (95% uncertainty interval [UI]: 6,243,599.2 to11,737,568.5) and 8,956,583.8 (6,446,323.9 to 12,364,520.8) prevalent cases of cancer in children under 5 years were identified worldwide; these cancers resulted in 44,451.6 (36,198.7 to 53,905.9) deaths and 3,918,014.8 (3,196,454.9 to 4,751,304.2) DALYs. From 1990 to 2019, although the numbers of incident and prevalent cases only decreased by -4.6% (-7.0 to -2.2) and -8.3% (-12.6 to -3.4), respectively, the numbers of deaths and DALYs clearly declined by -47.8% (-60.7 to -26.4) and -47.7% (-60.7 to -26.2), respectively. In 2019, the middle socio-demographic index (SDI) regions had the highest incidence and prevalence, whereas the low SDI regions had the most mortality and DALYs. Although all of the SDI regions displayed a steady drop in deaths and DALYs between 1990 and 2019, the low-middle and low SDI regions showed increasing trends of incidence and prevalence. Leukemia remained the most common cancer globally in 2019. From 1990 to 2019, the burdens of leukemia, liver cancer, and Hodgkin’s lymphoma declined, whereas the incidence and prevalence of other cancers grew, particularly of testicular cancer. Conclusions: The global childhood cancer burden in young children has been steadily decreasing over the past three decades. However, the burdens and other characteristics have varied across different regions and types of cancers. This highlights the need to reorient current treatment strategies and establish effective prevention methods to reduce the global burden of childhood cancer.